Professional Communication as a Manifestation of the Punctuation Culture of Media Workers - Shulska, Nataliia; Novikova, Olha; Hrytsevych, Yurii; Lychuk, Mariia; Vyshnevska, Galyna; Haida, Olha; Tarasenko, Serhii; Yavorskyi, Andrii (My University, 2023)
The article examines the written professional communication of media workers regarding punctuation literacy. It is noted that a successful portrait of a modern specialist forms linguistic literacy as a manifestation of professional competence, and compliance with the norms of modern literary language is a prerequisite for quality and full-fledged activity of Ukrainian mass media. The insufficient level of linguistic culture of the employees of the printed or electronic publication has a negative effect on the language literacy of the readers. It has been observed that the mega-fast pace of information broadcasting has a harmful effect on the language presentation of media texts at the orthographic, grammatical, and stylistic levels. Punctuation errors are a productive, representative, error-prone place in journalistic materials. It has been revealed that exemplary written communication involves strict observance of punctuation norms, that is, the correct use of punctuation marks in the text, which, in order to achieve the goal of communication, make it possible to logically and syntactically divide the statement into separate content elements. In the structure of the professional profile of a media worker, punctuation competence is defined as a sub-competency of professional linguistic and communicative competence. Based on the analyzed journalistic texts of all-Ukrainian and regional online mass media for the years 2019–2023, it was found that the authors use punctograms mechanically, without observing the basic rules of separation. The punctuation skills that modern media specialists must possess are outlined: 1) the ability to find content segments that need to be punctuated; 2) the ability to place punctuation marks in accordance with basic language rules; 3) skills of justifying the choice of a punctuation mark; 4) editorial work on correcting errors. Improving the editing process and increasing the communicative effectiveness of the media text should be facilitated by the use of the anti-error device by media workers, which contains data on error-prone places at the punctuation level.
Keywords: professional communication; language culture; punctuation; media worker; mass media; professional competence